Retracing Homophobic Tendencies in Two Central American Novels: Héctor Tobar’s The Tattooed Soldier and Javier Payeras’ Ruido de Fondo - Byrne, Matthew (2016)
The research article delves into the underlying heterosexism and homophobia of two Central American novels, Ruido de fondo (2006) and The Tattooed Soldier (1995), and retraces the origins of these notions to the Spanish colonial womb. These notions grew from patriarchal, sexist views of gender imposed on indigenous Central American societies. Before Columbus’ fateful arrival in the Americas in 1492, hierarchical organizations of humans did not exist. However, after the Spanish engineered various militaristic conquests, indigenous societies were forced to adopt Spanish ideals. Soon after, the Spanish usurped the legal and penile systems in Central America, empowering them to govern morality in the region. With this power, the Spanish began to erase indigenous culture and cultivate these hierarchical, patriarchal, and heterosexist norms. Four centuries later, these norms are analyzed in the heterosexism of two contemporary Central American novels: Ruido de fondo and The Tattooed Soldier. The novels demonstrate how defamatory portrayals of homosexuals and the policing of masculinity in Central American society perpetuate and legitimize violence against and hatred of homosexuals.